Caracterização tecnológica de um ultramilonito da região de Marco-CE - Nascimento, Débora Macêdo do (2014)
This dissertation presents the mineralogical and technological characteristics of the Granite Tucunduba, commercially known as Green Galaxy, located in the municipality of Marco - CE. Technological tests of physical indexes (bulk density, apparent porosity and water absorption apparent d'), uniaxial compression, bending in three and four points, AMSLER abrasive wear, impact and hard freezing and thawing body and speed of wave propagation were performed ultrasonic, based ABNT. To complement the data also quantified the rate of exhalation of radon. Radiometric measurement was performed by applying the active detection method exhalation gas for monitoring the amount of 222Rn. With the choice of the tests described, aimed to evaluate the quality of rock for use as ornamental stone. Was added to the main objectives of this work focused on the recognition of the mineralogical composition and textural features and the degree of microcracking of the material petrographic analysis. The petrographic analysis allowed to classify the rock as Ultramilonito feldspathic quartz. Macroscopically we can describe it as a rock of predominantly green. Their degree of microcracking settles around 1.8 / mm ². The results of technological tests showed that the rock has good quality for ornamental use and coating even in places with large temperature ranges. The radon exhalation rate was within the limits of the United States Environmental Protection Agency. Within this context, the Ultramilonito feldspathic quartz proved to be very tough for use as coating materials.